Disrupted in Schizophrenia 1 Regulates Ectopic Neurogenesis in the Mouse Hilus After Pilocarpine-induced Status Epilepticus. (1st July 2022) - Chen, Lu; Zhu, Lin; Xu, Jing; Xu, Puying; Han, Yanbing; Chang, Lvhua; Wu, Qian
Highlights: DISC1 expression was significantly down-regulated in the hilus after SE. In the hilus, DISC1 might regulate ectopic neurogenesis in pilocarpine-induced SE. The cell "encircling" indicated close relationship between DISC1 and astrocytes. Abstract: Augmentation of neurogenesis and migration of newly born neurons into ectopic regions like the hilus play critical roles during the pathophysiology of acute kindled seizures. Evidence shows that disrupted in schizophrenia 1 (DISC1) has an influence on adult neurogenesis in the dentate gyrus (DG); however, its role of regulating neurogenesis and mispositioned newborn neurons in the hilus after status epilepticus (SE) remains unknown. Using double immunofluorescence staining, the present study clarifies that DISC1 is co-expressed with nearly all of the neuronal markers, which are characterized by different stages of neuronal development, after pilocarpine-induced SE in mice. This reveals that DISC1 takes part in the modulation of neurogenesis in the hilus post-SE. Unexpectedly, an interesting phenomenon was observed as well. Some glial fibrillary acidic protein (GFAP)-positive cells in the hilus appeared to encircle the DISC1-positive cells, which possibly indicated that DISC1 may participate in the process of neuronal or neural development associated with astrocytes such as phagocytosis, dendritic spine development, synaptic transmission, and developmental and synaptic plasticity.